2016
DOI: 10.1111/anae.13564
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial comparing the effects of propofol with isoflurane in patients with diastolic dysfunction undergoing coronary artery bypass graft surgery

Abstract: There is a strong association between pre-operative diastolic dysfunction and difficulty in weaning from cardiopulmonary bypass. We compared the effects of propofol and isoflurane on left ventricular diastolic function in patients with pre-existing diastolic dysfunction undergoing coronary artery bypass grafting. We randomly allocated 60 patients to receive either propofol or isoflurane anaesthesia, and assessed left ventricular diastolic function using transoesophageal echocardiography. We measured early (E),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
(56 reference statements)
0
9
0
1
Order By: Relevance
“…However, many clinical studies have shown that patients with left ventricular diastolic dysfunction before anesthesia could be improved by using isoflurane, desflurane, or sevoflurane owing to reducing the after-load of the left ventricle to achieve a normal filling pattern (Sarkar, GuhaBiswas & Rupert, 2010). Ammar, A. reported that isoflurane was favourable over propofol on diastolic dysfunction (Ammar et al, 2016). It was possible that anesthetic agents could alter sarcoplasmic reticulum calcium homeostasis at the sarcoplasmic reticulum, a pivotal component of normally myocardial relaxation (Pagel et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, many clinical studies have shown that patients with left ventricular diastolic dysfunction before anesthesia could be improved by using isoflurane, desflurane, or sevoflurane owing to reducing the after-load of the left ventricle to achieve a normal filling pattern (Sarkar, GuhaBiswas & Rupert, 2010). Ammar, A. reported that isoflurane was favourable over propofol on diastolic dysfunction (Ammar et al, 2016). It was possible that anesthetic agents could alter sarcoplasmic reticulum calcium homeostasis at the sarcoplasmic reticulum, a pivotal component of normally myocardial relaxation (Pagel et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamics, variation of cardiac preload and afterload, was not a neglectable factor affecting diastolic function measurement, regardless of increase or decrease (Ammar et al, 2016). Accordingly, managing pro-load by monitoring CVP and managing after-load by controlling HR and MAP were applied to reduce the impact of hemodynamics on diastolic function measurement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Действительно, спустя 6, 12 и 24 мес были выявлены пациенты с различными жалобами, в том числе связанными с дискомфортом за грудиной, однако были и те, кто отмечал стойкие подъемы артериального давления. Следует отметить, что в ранние сроки после КШ может наблюдаться улучшение ДФ ЛЖ, связанное с влиянием ингаляционной анестезии на параметры релаксации миокарда [19,20]. Возврат к дооперационным значениям может быть связан с наличием у пациентов сопутствующей артериальной гипертензии (39 (97%)), а ухудшение или переход в другой тип дисфункции должен сопровождаться комплексным обследованием.…”
Section: оригинальные статьиunclassified